Tetrodotoxin levels in pufferfish (Lagocephalus sceleratus) caught in the Northeastern Mediterranean Sea. (1st November 2016) - Kosker, Ali Rıza; Özogul, Fatih; Durmus, Mustafa; Ucar, Yılmaz; Ayas, Deniz; Regenstein, Joe M.; Özogul, Yesim
Highlights: The first report of TTX levels in puffer fish from Northeastern Mediterranean Sea. TTX content in puffer fish was determined by mouse bioassay and LC–MS–MS methods. Changes in TTX levels in gonad, liver, intestine, skin and muscle of puffer fish. All of the gonads of female fish in all seasons were found to be toxic. Consumption of the puffer fish from Eastern Mediterranean Sea is very dangerous. Abstract: The toxicity of tetrodotoxin (TTX) in pufferfish ( Lagocephalus sceleratus ) from Mersin Bay in the Northeastern Mediterranean Sea was measured using a mouse bioassay (MBA) and LC–MS–MS. Pufferfish were caught by trawl fishing, longlining and fishing line from December 2012 to October 2013. Changes in the levels of TTX in the gonads, livers, intestines, skins and muscles as a function of season and sex were determined. The gonads of female fish were toxic in all seasons (>2 μg/g), whereas the gonads of male fish were only toxic in the spring and autumn. The highest TTX levels in gonads, livers, intestines and skins of female fish were 52.1, 46.2, 7.64 and 3.43 μg/g, respectively, using LC–MS–MS. The TTX level in the muscle of female fish in winter was 2.83 μg/g but was otherwise below the toxic limit. Consequently, it can be dangerous to consume pufferfish, including the edible muscle, from the Eastern Mediterranean Sea.